Buddhism a historical and practical vision : Buddhist Studies Conference, Delhi 1st July, 2023 - Buddhist Studies Conference 2023 Delhi; Thich Hanh Chanh; Bhikkhuni Gioi Huong 1963- (Delhi Eastern Book Linkers, 2023)
Papers presented at Buddhist Studies Conference on "Buddhism: a Historical and Practical Vision" held at Delhi on 1st July, 2023, organized by Hu'o'ng Sen Buddhist Temple, Paris, France
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Buddhism -- History -- Congresses; Buddhism -- Doctrines -- Congresses; Konferenzschrift